Compact, Wide Stopband, Shielded Hybrid Filter Based on Quarter-Mode Substrate Integrated Waveguide and Microstrip Line Resonators - Zheng, Yan; Zhu, Yilong; Wang, Zhan; Dong, Yuandan (IEEE microwave and wireless components letters, 2021)
A novel miniaturized bandpass filter (BPF) with high stopband rejection based on a hybrid structure is proposed with shielded quarter-mode substrate integrated waveguide (QMSIW) and microstrip technologies. The shielded QMSIW cavity provides a high-quality ( Q ) factor with substantial size reduction. This filter exhibits flexible response with four poles and two controllable transmission zeros (TZs) by incorporating two quarter-wavelength microstrip resonators into two back-to-back QMSIW resonators. The working principles for higher order mode suppression and filter coupling topology are carefully illustrated by eigen-mode simulation, coupling matrix, and field distribution analysis, respectively. Compared with the reported works, the proposed four-order BPF demonstrates advantageous features in terms of a compact size of 0.62\,\,λ _{0}× 0.62 \,\,λ _{0} , a low insertion loss of 1.2 dB, a wide passband (22.7%), and a high stopband rejection (better than 36 dB).